2004
DOI: 10.1258/0004563042466758
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin phenotype as a predictive factor of mortality in diabetic haemodialysis patients

Abstract: Hp phenotype may be useful in the risk stratification algorithm and management of DDPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…After screening the headings and abstracts, five studies finally met the inclusion criteria [1517,21,13]. For the interventional meta-analysis, eight records were retrieved using the electronic search strategy of this review, of which one [15] was included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the headings and abstracts, five studies finally met the inclusion criteria [1517,21,13]. For the interventional meta-analysis, eight records were retrieved using the electronic search strategy of this review, of which one [15] was included.…”
Section: Resultsmentioning
confidence: 99%
“…A post hoc exclusion of studies assessing specific medical scenarios such as heart failure and acute coronary events [16,17,21] did not affect the robustness of the results.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…There is evidence establishing Hp 2-2 as a predictor of CVD in diabetes mellitus [20, 21]. However, results are inconsistent regarding Hp genotypes and cardiovascular mortality in patients with CKD [22, 23]. A study in patients with ischemic heart disease (IHD) revealed a positive association between low HRV and Hp 2-2 [24].…”
Section: Introductionmentioning
confidence: 99%
“…An intermediate risk of CVD is associated with the Hp2/1 phenotype. [30][31][32] Furthermore, transgenic Hp2/2 mice on an apoEϪ/Ϫ background have more iron deposits and lipid peroxidation products as well as macrophage accumulation in atherosclerotic lesions compared with apoEϪ/Ϫ controls that have wild-type mouse Hp1/1 genotype. 33 Even intact erythrocytes can be a source of catalytically active heme.…”
Section: Low-density Lipoprotein Oxidation By Hemementioning
confidence: 99%